E-029 LVIS JR. stent for treatment of intracranial aneurysms with parent vessel diameter 2.5 mm or less. (22nd July 2018) - Santillan, A; Boddu, S; Schwarz, J; Lin, N; Gobin, Y; Knopman, J; Patsalides, A
Abstract : Background and purpose: This retrospective study evaluates the safety, effectiveness and long-term clinical and angiographic follow up of intracranial aneurysms treated with LVIS Jr. stent and parent vessels diameter equal or less than 2.5 mm. Materials and methods: We included all patients treated with LVIS Jr stent in aneurysms with small parent vessel diameter between March 2015 and July 2017. Periprocedural adverse events, immediate aneurysm occlusion rates and clinical and angiographic follow-up are reported. Results: A total of 35 patients with 35 aneurysms were included. Ten aneurysms were ruptured (28.6%) and 25 were unruptured (71.4%). The parent arteries measured 0.9 mm to 2.5 mm in diameter (mean, 2.2 mm). Intra-procedural thromboembolic complications occurred in 4 patients (11.4%) and an intra-operative aneurysm rupture in 1 patient (2.8%). Immediate complete aneurysm occlusion was noted in 21 out of 35 patients (60%). The clinical follow-up ranged between 1 and 25 months (mean, 10.5 months) and the MRA follow up ranged between 4 and 24 months (mean, 10.4 months). Complete aneurysm occlusion was achieved in 21 out of 29 patients (72.4%) at last angiographic follow-up (mean, 9.4 months; range 4 to 23 months). In-stent stenosis occurred in 1 out of 29 patients (3.4%), which was asymptomatic. From the 4 patients with in-stent thrombosis, 3 patients were treated with 'Y configuration' (2 patients with MCA aneurysms and 1 patient with an Acomm aneurysm). Mortality rate was 0%. Neurological morbidity was 2.9%. Disclosures: A. Santillan: None. S. Boddu: None. J. Schwarz: None. N. Lin: None. Y. Gobin: None. J. Knopman: None. A. Patsalides: None.